Autocorrelation of Spatial Based Dengue Hemorrhagic Fever Cases in Air Putih Area, Samarinda City - Syamsir, Syamsir; Pangestuty, Dwi Murdaningsih (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Dengue Hemorrhagic Fever (DHF) is the disease that spread quickly in tropical and subtropical regions. DHF can spread quickly because the dengue virus is transmitted through the Aedes aegypti and Aedes albopictus into the human body. One of the provinces that felt the impact of the dengue outbreak was East Kalimantan, especially Samarinda City. Efforts to prevent dengue have been attempted by health center officials in Samarinda City. The cause has not yet been effective in controlling DHF programs in Samarinda City because there is no mapping of DHF vulnerable areas. This study aims to map the pattern of DHF distribution in the working area of the health center to maximize the implementation of the DHF control program. Methods: The population in this study were all DHF sufferers registered at the Air Putih Health Center in 2018. Withdrawal samples using total sampling techniques. The analysis used in this study is spatial autocorrelation analysis by Moran’s I. The Moran Index method is used to determine the autocorrelation of the distribution of DHF cases. Result and Discussion: The results of the autocorrelation analysis showed a Z score <-Z α/2, meaning Ho was rejected. This shows that there is spatial autocorrelation in the distribution of DHF in the Health Center. Based on the Moran’s I value (Moran’s I = -0.045850) which has a negative value indicates that the distribution of DHF in the working area of the Health Center tends to spread or dispersed. Conclusion: This study concludes that the more cases of DHF in a densely populated area, the greater the chance of spatial autocorrelation. The closeness between DHF cases can form spatial autocorrelation with the dispersed category.